Episcopal acta in Normandy, 911-1204: the charters of the bishops of Avranches, Coutances and Sées - Allen, R (Boydell Press, 2015)
The launch of the British Academy’s English Episcopal Acta (EEA)project in 1973, and the publication of its first volume in 1980, along with the further forty-one that have since come to press, have helped to revolutionize our understanding of the English Church in the High Middle Ages.¹ Whereas previous generations of scholars interested in such documents had been forced to rely upon scattered, outdated and very often difficult-to-access published and unpublished material, those working today can depend upon a body of meticulously edited texts collected together in a single series that, upon its completion, will answer the call famously...